CUSTOMER SATISFACTION ANALYSIS OF THE BROMPIT AHASS APPLICATION USING THE CUSTOMER SATISFACTION INDEX (CSI) AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHODS - Zahrotul Firda; Indah Apriliana Sari Wulandari (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: There are a large number of motorcycle users in Indonesia, and of course, behind the many motorcycle users, they often experience problems with their vehicles. Many official and unofficial motorcycle repair shops in Indonesia, one of which is AHASS. AHASS is an official Honda motorcycle repair shop. Now AHASS provides an application called BROMPIT which has a function to make it easier for users to book services without having to queue, choose service schedules and other conveniences. With the large number of customers who use this application, of course, we also increasingly know the level of customer satisfaction when using this service. Method: The results of the calculation of the level of customer satisfaction in the Brompit AHASS application using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods have a value of 79.2, which means that customers feel "satisfied" with the application. Results: Meanwhile, the attributes that are prioritized for quality improvement are related to service information, speed of service response when booking, customer data security, application display and application performance. Novelty: This can be used as a suggestion for improvements related to the existing system to increase overall customer satisfaction and expectations.